PENGARUH INDEPENDENSI, KOMPETENSI DAN PROFESIONALISME AUDITOR INTERNAL TERHADAP KEMAMPUAN MENDETEKSI KECURANGAN (Studi Kasus Pada Bank Panin, Bank CIMB Niaga, dan Bank Nationalnobu - Jessica Puji Astuti; Partogian Sormin (Jurnal Akuntansi, 2019)
This study to examine the effect of independency, competency, and professionalism of internal auditor towards the ability to detects fraud. This study used purposive sampling method, and the sampling of this research are 98 internal auditor from Panin Bank, CIMB Niaga Bank, and Nationalnobu Bank.. The data were collected through questionnaire or survey methods. The analysis technique is multiple regression. The results show that partially independency, and professionalism of internal auditor has no significant effect towards the ability to detects fraud. While the competency has partial positive significant effect towards the ability to detects fraud. Simultaneously, independency, competency, and professionalism have significant effect toward the ability to detects fraud.